Building back better education systems: equity and COVID-19. Issue 3 (3rd November 2020) - Chapman, Christopher; Bell, Irene
Abstract : Purpose: The purpose of this article is to explore the relationship between the COVID-19 pandemic and the potential to use this challenging global context as an opportunity to build back better and more equitable educations systems. Design/methodology/approach: The approach taken involves drawing on the emerging literature to explore the relationship between COVID-19 and educational equity. Findings: The analysis undertaken involves the presentation of a typology framed by the quality of educational offer and the opportunity for engagement in the offer accompanied by four reflective questions for further consideration. Originality/value: The analysis presented here underpins the presentation of a heuristic typology designed to stimulate exploration and discussion relating to building back better, more equitable education systems after the COVID-19 pandemic.